Whistler Influence on the Overall Very Low Frequency Wave Intensity in the Upper Ionosphere. Issue 7 (4th July 2018) - Záhlava, J.; Němec, F.; Pincon, J. L.; Santolík, O.; Kolmašová, I.; Parrot, M.
Abstract: We investigate the influence of lightning‐generated whistlers on the overall intensity of electromagnetic waves measured by the Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions spacecraft (2004–2010, quasi Sun‐synchronous polar orbit with an altitude of about 700 km) at frequencies below 18 kHz. Whistler occurrence rate evaluated using an onboard neural network designed for automated whistler detection is used to distinguish periods of high and low whistler occurrence rates. It is shown that especially during the night and particularly in the frequency‐geomagnetic latitude intervals with a low average wave intensity, contribution of lightning‐generated whistlers to the overall wave intensity is significant. At frequencies below 1 kHz, where all six electromagnetic wave components were measured during specific intervals, the study is accompanied by analysis of wave propagation directions. When we limit the analysis only to fractional‐hop whistlers, which propagate away from the Earth, we find a reasonable agreement with results obtained from the whole data set. This also confirms the validity of the whistler occurrence rate analysis at higher frequencies. Key Points: Neural network on board DEMETER is used to distinguish periods with low and high whistler occurrence rate Frequency‐latitude intervals where the very low frequency wave intensity is dominated by lightning‐generated whistlers are identified At extralow frequencies, where wave propagation directions can be determined, the results are consistent between the two types of analysis